PERTUMBUHAN DAN MORFOLOGI KULTUR TUNAS SEMPUR (Dillenia philippinensis Rolfe) PADA MEDIA MS-BAP-NAA (Growth and Morphology of Sempur (Dillenia philippinensis Rolfe) Shoot Culture on MS –BAP-NAA Media) - Deritha Ellfy Rantau; Dyah Retno Wulandari; Tri Muji Ermayanti; Rudiyanto Rudiyanto; Betalini Widhi Hapsari; Aida Wulansari; Evan Maulana; Herlambang Laksmana Firdaus (Pusat Penelitian dan Pengembangan Hutan, 2021)
ABSTRACT Propagation of sempur (Dillenia philippinensis Rolfe) using conventional vegetative methods is considered ineffective due to slow process and low germination level. Propagation by tissue culture is considered more effective because it does not depend on the season and requires less plant material. It can benefit sempur conservation since it is categorized as threatened with extinction in 2020 on the IUCN red list. This study aimed to evaluate the effect of BAP and NAA on the growth of sempur’s shoots and to observe the morphology of shoot culture. The media used as a control was MS without growth regulators. The treatment medium was MS with the addition of BAP and NAA. Shoots were used as explants. Shoot growth and plantlet morphology were observed eight weeks after planting. The results indicated that the combination of 1 mg/l BAP and 0.5 mg/l NAA resulted in the highest total number of leaves, nodes and adventitious shoots. The combination of BAP and NAA, each 1 mg/l, resulted in the highest fresh weight and callus formation. The combination of 1 and 2 mg/l BAP and 0.5-1 mg/l NAA could not form roots. In comparison, the combination of BAP and NAA in culture media could change the shape and size of the leaves. The survival rate of growth of plantlets derived from MS medium was 50% at 22 weeks after acclimatization.Keywords: morphology, shoot culture, sempur, BAP (Benzil Amino Purin), NAA (Naphthalene Acetic Acid) ABSTRAK Perbanyakan tanaman sempur (Dillenia philippinensis Rolfe) dengan metode konvensional secara vegetatif memerlukan waktu lama dan daya kecambah biji juga rendah. Perbanyakan dengan kultur jaringan dianggap lebih menguntungkan karena tidak tergantung musim, memerlukan sedikit bahan tanaman dan bermanfaat untuk konservasi sempur karena termasuk spesies yang hampir terancam punah tahun 2020 dalam daftar merah IUCN. Penelitian ini bertujuan untuk mengevaluasi pengaruh BAP dan NAA terhadap pertumbuhan tunas sempur serta mengamati morfologi kultur tunas. Media yang digunakan sebagai kontrol adalah MS yang tidak mengandung zat pengatur tumbuh. Media perlakuan adalah MS dengan penambahan BAP dan NAA. Tunas pucuk dipergunakan sebagai eksplan. Pertumbuhan tunas dan morfologi planlet diamati pada delapan MST. Hasil pengamatan menunjukkan bahwa kombinasi 1 mg/l BAP dan 0,5 mg/l NAA menghasilkan jumlah total daun, buku dan jumlah tunas adventif tertinggi. Kombinasi BAP dan NAA masing-masing 1 mg/l menghasilkan bobot basah dan pembentukan kalus tertinggi. Kombinasi antara BAP 1 dan 2 mg/l serta NAA 0,5-1 mg/l tidak mampu membentuk akar. Kombinasi BAP dan NAA pada media kultur mengubah bentukan dan ukuran daun. Daya tumbuh planlet yang berasal dari media MS adalah 50% pada 22 minggu setelah aklimatisasi. Kata kunci: morfologi, kultur tunas, sempur, BAP (Benzil Amino Purin), NAA (Naphthalene Acetic Acid)